2018
DOI: 10.1002/phar.2115
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis for Chronic Pain: Challenges and Considerations

Abstract: The National Academies of Sciences, Engineering, and Medicine has found substantial evidence that cannabis (plant) is effective for the treatment of chronic pain in adults, and moderate evidence that oromucosal cannabinoids (extracts, especially nabiximols) improve short-term sleep disturbances in chronic pain. The paradoxical superiority of the cannabis plant over cannabinoid molecules represents a challenge for the medical community and the established processes that define modern pharmacy. The expanding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 66 publications
2
69
0
6
Order By: Relevance
“…Symptom relief as a result of MC treatment was prominent and distinctly noticeable for most of the patients. Relief of symptoms such as pain, anxiety, moodiness, and spasticity was evident, agreeing well with many previous studies [22,24,25,[32][33][34] . Relief was obtained not only for the specific indications serving as criteria for each patient, but also for additional symptoms and side effects (e.g., sleep disorders, ataxia, depression, and lack of appetite), as shown previously by Boehnke et al (2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Symptom relief as a result of MC treatment was prominent and distinctly noticeable for most of the patients. Relief of symptoms such as pain, anxiety, moodiness, and spasticity was evident, agreeing well with many previous studies [22,24,25,[32][33][34] . Relief was obtained not only for the specific indications serving as criteria for each patient, but also for additional symptoms and side effects (e.g., sleep disorders, ataxia, depression, and lack of appetite), as shown previously by Boehnke et al (2016).…”
Section: Discussionsupporting
confidence: 92%
“…The main conclusion is generally that substitution of traditional pain medications with MC causes fewer side effects 119 and an improvement in medical symptoms [19,21,22] . Some studies have shown the replacement of other prescription pharmaceuticals by MC as well [23][24][25] . However, it is important to emphasize that many of those studies were limited in terms of statistical indexes, database volume, and the perspective of time, calling for further exploration [26] .…”
Section: Introductionmentioning
confidence: 99%
“…We recognize that other factors could be at play in the selection of high potency cannabis in medicinal programs. For one, more potent products are better regarded in recreational cannabis practices [13], and this might influence the election of high THC products by recreational users [48]. Furthermore, since the price of a product increases with increasing THC concentration, revenue could contribute to budtender recommendations [29,49].…”
Section: Plos Onementioning
confidence: 99%
“…Inhaled cannabis has been proven effective for the treatment of various types of chronic pain ranging from neuropathic pain to diabetic nephropathy and has a more favorable pharmacokinetic profile than oral formulations [11][12][13][14][15]. Thus, knowing what type of cannabis herbal products are offered online is relevant for pain patients.…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal cannabis clinical experiences and legal use have emerged during the last few decades ( 2 ). For its pain-relieving and appetite-stimulating properties ( 3 ), we found cannabis suitable for tackling severe neuropathic pain, severe muscular emaciation, anorexia, disturbed sleep patterns and changes in the patient’s mood.…”
Section: Introductionmentioning
confidence: 99%